Web-Based SIMKAH Implementation at KUA: A Multi-City Comparative Study of Legal Effectiveness in Indonesia - Hasyim Sofyan Lahilote; Aditya Zahran Bachdar; Faradila Hasan; Abdul Fajri Kolopita (Al-Ahkam, 2026)
Marriage registration in Indonesia is a legal obligation under Law Number 16 of 2019, yet millions of Muslim couples remain legally unregistered despite formal prohibition. This study examines web-based SIMKAH (Marriage Management Information System) implementation under Minister of Religious Affairs Decree Number 892 of 2019 at Religious Affairs Offices (KUA) in Surakarta, Gorontalo, and Manado — three cities representing distinct geographical, demographic, and administrative contexts across two Indonesian islands. Using a qualitative descriptive approach with empirical legal methodology, data were collected through in-depth interviews with twelve purposively selected informants and analyzed thematically. Findings confirm that all three KUAs have implemented SIMKAH effectively at the counter level, with measurable improvements in processing speed, data accuracy, and public accessibility. However, SIMKAH does not automatically synchronize with the national civil registration system (SIAK) or the Religious Court, creating a consequential inter-institutional data gap. The study recommends a cross-ministerial regulatory instrument mandating real-time SIMKAH–SIAK–Religious Court integration, continuous operator training, and community-based public socialization.